LABOUR MOTIVATION: AN AXIOMATIC VECTOR MODEL - Kotliarov, Ivan (Anales de Psicología / Annals of Psychology, 2008)
The present article gives a list of axioms needed for building up a mathematical theory of human motivation. A mathematical model of labour motivation is proposed. Motivation is represented as a resulting vector of partial motivation generated by specific groups of needs. Vroom’s model is included in the proposed model as instant motivation. A correlation between the expenses on motivation, the level of motivation and the level of productivity is established.